Cascade or echo chamber? A complex agent-based simulation of voter turnout. (March 2016) - Fieldhouse, Ed; Lessard-Phillips, Laurence; Edmonds, Bruce
Using an agent-based simulation of electoral participation, this paper examines the second order or cascade effects of an exogenous increase in turnout. Unlike most previous applications of agent-based modelling in political science, we adopt a descriptively complex rather than a simple model of behaviour. Experimenting with different levels of mobilisation allows estimation of the extent to which mobilisation spreads beyond the primary mobilisation target across the population as well as whether or not it survives over time. We argue that in a complex world cascade effects are smaller than previously thought. However, mobilisation effects can create secondary effects through habitual voting and increases in political interest and party affiliation, which reverberate over time, creating long-term spillover effects.